Tanggung Jawab Pt Pegadaian Syariah terhadap Kehilangan Jaminan Atas Produk Arrum BPKB Pada PT. Pegadaian Syariah Kecamatan Oebobo Kota Kupang - Rizan Rafsanjani S; Siti Ramlah Usman; Petornius Damat (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The purpose of this research is to analyze the responsibility of PT. Pegadaian Syariah towards the loss of collateral for Arrum BPKB Products at PT. Pegadaian Syariah Oebobo District Kupang City. The type of research used by the author is Empirical Legal research, the type of data used in this research is qualitative data. The data used in the research based on the relevance of the source data, namely primary, secondary and tertiary data. The result of this research is that the responsibility of PT Pegadaian Syariah towards the loss of collateral for Arrum BPKB products at PT Pegadaian Syariah Oebobo District Kupang City, that the implementation of responsibility has been going well but is still not optimal regarding the implementation and responsibility services provided by PT Pegadaian Syariah Oebobo District Kupang City due to several factors. Factors that cause PT Pegadaian Syariah Oebobo Subdistrict Kupang City is not responsible for the loss of collateral for Arrum BPKB products at PT Pegadaian Syariah Oebobo Subdistrict Kupang City, namely if the loss of collateral for Arrum BPKB is caused by mistakes made by customers then PT Pegadaian Syariah Oebobo Subdistrict Kupang City is not responsible but if the loss of collateral for Arrum BPKB is caused by mistakes made by PT Pegadaian Syariah Oebobo Subdistrict Kupang City then PT Pegadaian Syariah Oebobo Subdistrict Kupang City is responsible for mistakes that occur.